Soft Tissue Balancing in Total Knee Arthroplasty - Matsuda, Shuichi; Lustig, Sébastien; van der Merwe, Willem (Springer Berlin Heidelberg : Imprint: Springer, 2017)
In this booklet, experts from across the world, including members of the ISAKOS Knee Arthroplasty Committee, offer clear, up-to-date guidance on all aspects of soft tissue or ligament balancing in primary total knee arthroplasty with the aim of enabling the reader to achieve optimal patient outcomes. After an introduction explaining the normal soft tissue condition in the native knee, surgical procedures are described, including techniques for the management of severe deformity. The most striking feature of the booklet, however, is the many pages devoted to the accurate evaluation and clinical relevance of ligament balancing. Different techniques and devices for intraoperative soft tissue assessment are discussed, highlighting, for example, the use of gap-measuring devices or trial liners with load-bearing sensors to achieve more objective evaluation. Above all, special attention is devoted to the crucial issue of the impact of intraoperative soft tissue balance on postoperative results. In the closing chapter, very experienced surgeons introduce intraoperative troubleshooting in order to assist successful completion of arthroplasty.
Keywords: Medicine.; Orthopedics.; elektronické knihy; electronic books